2017
DOI: 10.1016/j.pld.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Holttumochloa (Poaceae: Bambusoideae) in China with description of a new species revealed by morphological and molecular evidence

Abstract: Holttumochloa has previously only been recorded from Malaysia. Here we describe and illustrate a new species, Holttumochloa hainanensis sp. nov., from the lowland montane forests of Diaoluo Mountain on the Island of Hainan, South China. Morphologically, H. hainanensis is similar to Holttumochloa korbuensis, but can be clearly distinguished from it in having larger culms covered by white wax, longer leaf blades, larger pseudospikelets and anthers. Furthermore, molecular phylogeny based on the nuclear gene GBSSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In addition, the authors also confirmed the position of Bambusa , Dendrocalamus , Gigantochloa Kurz ex Munro, Melocalamus Benth., Neosinocalamus Keng f., Oxytenanthera Munro and Thyrsostachys Gamble as a closely related group of Bambusinae. Zhou et al. (2017a) used morphology and molecular phylogeny to describe and illustrate a new species of Holttumochloa K. M. Wong from the lowland montane forests of Diaoluo Mountain on the Island of Hainan, South China, namely, Holttumochloa hainanensis M. Y. Zhou & D. Z. Li.…”
Section: Progress Of Taxonomy At Kibmentioning
confidence: 99%
“…In addition, the authors also confirmed the position of Bambusa , Dendrocalamus , Gigantochloa Kurz ex Munro, Melocalamus Benth., Neosinocalamus Keng f., Oxytenanthera Munro and Thyrsostachys Gamble as a closely related group of Bambusinae. Zhou et al. (2017a) used morphology and molecular phylogeny to describe and illustrate a new species of Holttumochloa K. M. Wong from the lowland montane forests of Diaoluo Mountain on the Island of Hainan, South China, namely, Holttumochloa hainanensis M. Y. Zhou & D. Z. Li.…”
Section: Progress Of Taxonomy At Kibmentioning
confidence: 99%
“…Howev-er, due to the unpredictable flowering period and substantial variation in flowering patterns, classifying this subfamily poses greater challenges [1][2][3][4][5][6][7][8]. Therefore, the distinctive characteristics of the subfamily, such as culm, rhizome, branch, and culm sheath, have traditionally been employed in taxonomic classification [2][3][4][9][10][11][12][13][14][15][16][17]. From a scientific perspective, the validation of this classification requires further research.…”
Section: Introductionmentioning
confidence: 99%